2019
DOI: 10.1080/22423982.2019.1573163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pilot paediatric concussion telemedicine programme for northern communities in Manitoba

Abstract: Pediatric concussion patients living in northern communities in Canada can face unique challenges accessing primary and specialized healthcare. In this study we report the clinical characteristics, healthcare utilization, outcomes and estimated cost avoidance associated with a pilot pediatric concussion telemedicine program established between a multi-disciplinary pediatric concussion program in Winnipeg, Manitoba and a hospital in Thompson, Manitoba. From October 1st- July 1st, 2018, 20 patients were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 54 publications
(72 reference statements)
2
49
0
2
Order By: Relevance
“…All patients evaluated through this program undergo medical assessment and management by a neurosurgeon who works closely with provincial experts in neuropsychology, exercise science, vestibular and cervical spine physiotherapy, neurology, neuro-ophthalmology, radiology and adolescent psychiatry. To improve access to care among paediatric patients living in northern and remote communities in Manitoba, the Pan Am Concussion Program partnered with Thompson General Hospital to develop a pilot project of a paediatric concussion telemedicine program (now termed the Pan Am Clinic CONcussion in the North EConsultation and Telemedicine, CONNECT Program) [13]. The distance between the two centres is approximately 760 km, which is an 8-10-h drive (depending on seasonal road conditions) or a 1.5-h flight by airplane.…”
Section: Preliminary Experience Of the Pan Am Clinic Connect Programmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients evaluated through this program undergo medical assessment and management by a neurosurgeon who works closely with provincial experts in neuropsychology, exercise science, vestibular and cervical spine physiotherapy, neurology, neuro-ophthalmology, radiology and adolescent psychiatry. To improve access to care among paediatric patients living in northern and remote communities in Manitoba, the Pan Am Concussion Program partnered with Thompson General Hospital to develop a pilot project of a paediatric concussion telemedicine program (now termed the Pan Am Clinic CONcussion in the North EConsultation and Telemedicine, CONNECT Program) [13]. The distance between the two centres is approximately 760 km, which is an 8-10-h drive (depending on seasonal road conditions) or a 1.5-h flight by airplane.…”
Section: Preliminary Experience Of the Pan Am Clinic Connect Programmentioning
confidence: 99%
“…Over the past two decades, telemedicine has emerged as a valuable tool that can enhance access to specialised healthcare for patients with a wide spectrum of neurological disorders including acute stroke, headache, epilepsy and mental health disorders [11,12]. More recently, preliminary research has demonstrated that telemedicine can provide timely access to safe and cost-effective paediatric concussion care within medically underserved communities [13]. Similar to established systems of care for acute stroke, additional work suggests that telemedicine-based networks may provide an innovative approach that connects paediatric concussion patients living in rural, remote and isolated communities to regional multi-disciplinary concussion programmes located in distant urban settings [14].…”
mentioning
confidence: 99%
“…One such pilot program using Veterans Health Administration referrals to a central subspecialty service found similar survival with telepresence consultations and in‐person visits and a marked reduction in patient mortality across early‐ and late‐stage liver disease in propensity‐matched cohorts without any visit, particularly for rural patients . Subspecialty care through dispersed networks have shown telemedicine and spoke‐and‐hub referral systems to be highly cost‐effective in other disease settings . Another strategy to contain costs and facilitate patient referral and follow‐up would be the employment of patient navigators, who have been proven to reduce unnecessary emergency department visits and readmissions in other settings …”
Section: Discussionmentioning
confidence: 99%
“…(30) Subspecialty care through dispersed networks have shown telemedicine and spoke-and-hub referral systems to be highly cost-effective in other disease settings. (31)(32)(33) Another strategy to contain costs and facilitate patient referral and follow-up would be the employment of patient navigators, who have been proven to reduce unnecessary emergency department visits and readmissions in other settings. (34,35) Our findings support those of previous studies that demonstrated the importance of hospital-level characteristics to outcomes among patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…No Canadá, por exemplo, dada suas peculiaridades climáticas e geográficas, desenvolveram tecnologia capaz de transmitir laudos, prontuários e dados inerentes aos tratamentos de pacientes, sem perdas, além de conectar centros mais especializados com localidades carentes de atendimento especializado (Khouri, 2003). O governo canadense foi um grande investidor para o desenvolvimento e aplicação de tecnologias que promovesse o aumento ao acesso de atendimentos especializados pelo país (House & Roberts, 1977;Ellis et al, 2019).…”
Section: Oms (2010)unclassified